2017
DOI: 10.1080/07391102.2017.1404938
|View full text |Cite
|
Sign up to set email alerts
|

Computational analyses of interactions between ALK-5 and bioactive ligands: insights for the design of potential anticancer agents

Abstract: Activin Receptor-Like Kinase 5 (ALK-5) is related to some types of cancer, such as breast, lung, and pancreas. In this study, we have used molecular docking, molecular dynamics simulations, and free energy calculations in order to explore key interactions between ALK-5 and six bioactive ligands with different ranges of biological activity. The motivation of this work is the lack of crystal structure for inhibitor-protein complexes for this set of ligands. The understanding of the molecular structure and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…After the MD simulations, the most stable sub-trajectories of the five ALK-5-inhibitor structures were selected (20 ns for each complex) for binding free energy calculations using the SIE method. These results are presented in Table 1 along with the ∆G value for the benchmark compound (4-( [1,2,4]triazolo [1,5-a]pyridin-6-yl)-N-(4-methoxyphenyl)-3-(6-methylpyridin-2-yl)-1H-pyrazole-1carbothioamide), which is a known ALK-5 inhibitor (IC 50 = 0.57 nM) [53]. The binding free energies were calculated and compared with the values obtained from the docking simulations, as reported in Table 1.…”
Section: Binding Free Energymentioning
confidence: 99%
“…After the MD simulations, the most stable sub-trajectories of the five ALK-5-inhibitor structures were selected (20 ns for each complex) for binding free energy calculations using the SIE method. These results are presented in Table 1 along with the ∆G value for the benchmark compound (4-( [1,2,4]triazolo [1,5-a]pyridin-6-yl)-N-(4-methoxyphenyl)-3-(6-methylpyridin-2-yl)-1H-pyrazole-1carbothioamide), which is a known ALK-5 inhibitor (IC 50 = 0.57 nM) [53]. The binding free energies were calculated and compared with the values obtained from the docking simulations, as reported in Table 1.…”
Section: Binding Free Energymentioning
confidence: 99%
“…The initial conformation of each ligand-receptor complex, used in the QM/MM (quantum mechanics/molecular mechanics, using the ONIOM method) calculations, was previously obtained [8], and, for these calculations, we employed Gaussian09 [33]. Initially, the binding site of ALK-5 was delimited at a radius of 5 Å, and this cut was done by using Pymol [34].…”
Section: Oniom Analysesmentioning
confidence: 99%
“…Several studies have shown that the ALK-5 inhibition is related to various types of tumors, such as pancreatic, breast and colon, and these studies have been done to induce the inhibition of TGF-β signaling [7][8][9]. In this paper, six molecules ((1 (4-( [1,2,4] triazole [1,5-a] Escola de Artes, Universidade de São Paulo Ciências e Humanidades, Av.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies attempt to inhibit the biological targets under study and one way to study the interaction processes between HER-2/EGFR and inhibitor molecules is employing molecular modeling methods, which are often employed in medicinal chemistry [6,13,14,15,16]. Using these techniques, it is possible to identify the interactions that occur between bioactive molecules and biological receptors.…”
Section: Introductionmentioning
confidence: 99%